The Predicate Semantic with Linguists An Anajytical Study - Naseer Thojeel Dawood ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The study  deals with the definition of the predicate ــ according to the rationalists ( the logicians ) and  Akhbaris (the linguists  and fundamentalists ) ــ an analytical study ، with mentioning its most prominent nomenclature،  its types ، the criterion of truthfulness and falsehood in it، and the opinions  of the two teams on the difference between complete andincomplete predicate ، as well as the sections of the sentence as an analysis and discussion، We  come to the conclusion that the fundamentalists  search  was an in-depth study  that seeks to delve into the depths of the sentence in order to examine  it،  and reveal its hidden connotations .And this is what made one of the scholars to describe the grammatical research of thefundamentalists as (semantics).DOI /10.54633/2333-021-042-015